Unique Peptide Patterns in SARS-CoV-2 Virus Proteins Provide Insights into Variants’ Ability to Evade Immune Response and Infect Humans - Evangelos Kontopodis; Vasileios Pierros; Dimitrios J. Stravopodis; George Th. Tsangaris (Advanced Research in Biological Science Vol. 1, 2023)
The ongoing SARS-CoV-2 pandemic has created a need to identify particular regions within the viral proteome that can serve as antigenic sites and ptomising targets for treatment. In this study, we employed a novel approach to shed light on the interactions between the virus and the host organism. We focused on analyzing the Unique Peptides (UPs) of the virus, specifically those with a minimum amino acid sequence length named as Core Unique Peptides (CrUPs), not in relation to the virus itself, but in comparison to the entire proteome of the host organism. Through this approach, we successfully identified CrUPs unique to the virus, which were not found in the host organism’s proteome. We specifically examined the SARS-CoV-2 proteome to identify CrUPs that interact with the human proteome, referred to as C/H-CrUPs. Our findings indicate that SARS-CoV-2 contains 7,503 C/H-CrUPs, with the protein SPIKE_SARS2 exhibiting the highest density of these peptides. Extensive analysis revealed that the critical P681R mutation generates new C/H-CrUPs in the vicinity of the R685 cleavage site, while the L452R mutation diminishes the antigenicity of the NF9 peptide and enhances the virus’s binding affinity to its ACE2 receptor protein. The simultaneous presence of these mutations in concerning variants like Delta enables the virus to evade the immune response, facilitates its entry into host cells on a larger scale, significantly increases virus production, and results in its widespread release, thereby elevating its infectivity in human target cells.The Core Unique Peptides (CrUPs) approach utilized in this study has the potential to be applied to any virus or pathogen targeting any host organism, yielding valuable insights into their immune response and infectiveness.